Oceanic archipelagos: a perspective on the geodynamics and biogeography of the World’s smallest biotic provinces - Kostas Triantis; Robert J. Whittaker; José María Fernández-Palacios; Dennis J. Geist (Frontiers of Biogeography)
Since the contributions of Charles Darwin and Alfred Russel Wallace, oceanic archipelagos have played a central role in the development of biogeography. However, despite the critical influence of oceanic islands on ecological and evolutionary theory, our focus has remained limited to either the island-level of specific archipelagos or single archipelagos. Recently, it was proposed that oceanic archipelagos qualify as biotic provinces, with diversity primarily reflecting a balance between speciation and extinction, with colonization having a minor role. Here we focus on major attributes of the archipelagic geological dynamics that can affect diversity at both the island and the archipelagic level. We also re-affirm that oceanic archipelagos are appropriate spatiotemporal units to frame analyses in order to understand large scale patterns of biodiversity.